The Efficacy of the ‘My Darling’ Family Planning App in Reducing Unmet Postpartum - Virawati, Dini Indo; Lushinta, Lidia; Sinaga, Elisa Goretti (Borneo Scientific Publishing, 2026)
Unmet need for family planning is highest among women during the first year postpartum, reflecting gaps in access to effective counselling services, particularly during the COVID-19 pandemic. Integrating family planning counselling into antenatal and postnatal care has been proposed as a strategy to improve service efficiency and accessibility. Therefore, this study aimed to identify the family planning counselling needs of pregnant women during the COVID-19 pandemic, develop an online counselling application (“My Darling KB”), and evaluate its effectiveness in reducing postpartum unmet need for family planning. This study employed a quantitative experimental approach using a randomized controlled trial (RCT) design. A total of 150 pregnant women from four selected clinics in Samarinda City were randomly allocated to either the intervention or control group, with 75 participants in each group. The intervention group received counselling through the “My Darling KB” application, while the control group received standard care. The results showed that baseline characteristics between the intervention and control groups were comparable. The use of the “My Darling KB” application significantly reduced postpartum unmet need for family planning. Furthermore, pregnant women who received counselling through the application demonstrated a higher intention to use modern contraceptive methods compared to those in the control group. In conclusion, the “My Darling KB” application is an effective digital intervention for improving family planning counselling and reducing postpartum unmet need for contraception. This approach offers a promising strategy to enhance access to reproductive health services, particularly in contexts with limited face-to-face interaction, such as during the COVID-19 pandemic.